Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae) - Tutman, Pero; Freyhof, Jörg; Dulčić, Jakov; Glamuzina, Branko; Geiger, Matthias (Zootaxa, 2017)
Lampetra soljani, new species, is described from the lower Neretva River in the Adriatic Sea basin. Previously it was identified as L. zanandreai. Based on morphological similarity and mitochondrial genetic data, it is related to L. lanceolata and L. ninae from the Black Sea basin. Lampetra soljani is distinguished from all other species of Lampetra by having a marmorate flank pattern in live, fully grown ammocoetes, and in some adults (vs. plain colour pattern). Lampetra soljani is distinguished from other Lampetra species by having three velar tentacles, 54–57 trunk myomeres between the last branchial opening and the anus, no posterial teeth and a bicuspid middle endolateral tooth. Lampetra soljani is also well distinguished by COI barcode data from its congeners. The new species is widespread in the Neretva River drainage and lampreys from Lake Skadar basin are likely to belong to this species also.